Simple and rapid detection of free 3-monochloropropane-1, 2-diol based on cysteine modified silver nanoparticles. (15th February 2021) - Martin, Aka Alla; Fodjo, Essy Kouadio; Marc, Gouli Bi Irié; Albert, Trokourey; Kong, Cong
Graphical abstract: Highlights: Cysteine-modified silver nanoparticles (Cys-AgNPs) was used for 3-MCPD detection. Both colorimetric and naked eye detection with this Cys-AgNPs are feasible for 3-MCPD detection. The sensing process needs only 5 min at 100 °C. Abstract: A rapid colorimetric method using cysteine-modified silver nanoparticles (Cys-AgNPs) is applied for the detection of 3-monochloropropane-1, 2-diol (3-MCPD). Indeed, in the presence of 3-MCPD, the color of Cys-AgNPs solution changes from yellow to pink within five minutes at 100 °C and pH 9.3. This change is mainly attributed to the ability of amino group of cysteine to react with 3-MCPD to form N-(2, 3-dihydroxypropyl)-amino acid grafted on AgNPs (3-MCPD-Cys-AgNPs) in alkaline medium. This color change makes 3-MCPD to be clearly detectable by unassisted visual means even at 0.1 μg⋅mL −1 . Besides, using UV–Vis spectroscopic technique, a linear range from 0.1 μg⋅mL −1 to 1.25 μg⋅mL −1 for 3-MCPD detection is obtained, with a calculated detection limit of 0.084 μg⋅mL −1 . These results suggest that this sensing technique is sensitive to 3-MCPD and may have a substantial application in the rapid detection of food contaminants particularly, where quality and safety of food products are paramount concern.